Comparison of colon adenoma detection rates using cap-assisted and Endocuff-assisted colonoscopy: a randomized controlled trial - Marsano, Joseph; Johnson, Sheeva; Yan, Stephanie; Alli-Akintade, Latifat; Wilson, Machelle; Al-Juburi, Amar; Stondell, Jesse; Tejaswi, Sooraj (Endoscopy International Open, 2019)
Objectives and study aim Colonoscopy prevents colorectal cancer by removing adenomatous polyps, but missed adenomas lead to interval cancers. Different devices have been used to increase adenoma detection rates (ADR). Two such devices of interest are the transparent cap (Olympus) and Endocuff (ARC Medical). Our study aimed to compare differences in ADR between Endocuff-assisted colonoscopy (EAC), cap-assisted colonoscopy (CAC) and standard colonoscopy (SC). Patients and methods A sample size of 126 subjects was calculated to determine an effect size of 30 %. Patients undergoing screening or surveillance colonoscopy between March 2016 and January 2017 were randomized to SC, CAC or EAC groups. Three experienced endoscopists performed all colonoscopies. Patient demographics, procedure indication, Boston Bowel Prep Score (BBPS), withdrawal time, polyp size, location, histopathology, were analyzed.Results There was no difference in ADR (52 %, 40 % and 54 %) in the SC, CAC and EAC groups respectively (P = 0.4). Similar findings were also observed for proximal ADR (45 %, 35 %, and 50 %, P = 0.4) and SSA detection rate (16 %, 14 %, and 23 %, P = 0.5). EAC detected higher mean ADR per colonoscopy compared to CAC (1.70 vs 0.76, P = 0.01). However, there was no significant difference in mean ADR per positive colonoscopy (2.08, 1.63, and 2.59, P = 0.21). Conclusion In a randomized controlled trial comparing AC to CAC and SC, neither device conferred additional benefits in ADR among high detectors. When comparing each device, EAC may be better than CAC at detecting more total adenomas.